Participação, sociedade civil e a capacidade de influenciar políticas sociais : o caso do Conselho Municipal de Educação da Serra (CMES) - Ferreira, Andreza Alves (2006)
The present work analyses the relationship among civil society and his capability to influence social policies through a case study the City Council of Education of Serra (CMES). It is looked to evaluate these spaces represent a new standard of relationship between State and Civil Society, leading to an effective participation of citizens since that the historical pattern had been a closed one, only admitting the participation of governmental agents. It argues that the process in course in the CMES have extended the debate, reverberating in the ears of society and, so, permitting a wide visibility of the educational policies, mainly if compared with the previous periods (until middle of the decade of 1990). The experience of CMES has made possible technical and political apprenticeship in educational policies at local level. In spite of these positive aspects, it concludes that political participation of citizens is quite limited and, in the most of the cases, restricted to few organizations that have assent in the Council. Since the low level of communication between these organizations and their members and the population in general, the defense of public interests is jeopardized for these are eclipsed by particular and corportative interests.